"Banditry and Subversion" in a Classroom Game. (3rd July 2017) - Schneewind, Sarah
Abstract : In the context of a course on Ming working lives, a classroom game requiring no fancy equipment enables students to think through the complex relations of the imperial house and palace eunuchs, commanders and soldiers, bandits and merchants, Mongols and Han folk, as portrayed in David Robinson's work on the capital area and other Ming scholarship.